Extraction of glycolic acid from natural sources - Faznurfariza, Firdaus@Nicholas (2012)
Glycolic acid (GA) is a type of alpha hydroxyacetic acid (AHA).It is a small molecule of AHA that is colorless, odorless and hygroscopic. Since GA is capable of penetrate the skin,it is suitable for exfoliate and anti ageing application.It is widely used especially in dermatology, medical and pharmaceutical applications.Since GA is very useful in cosmetic and pharmaceutical field, it yields a high market demand.By using rotten fruits obtained from the market as the sources to produce GA, the waste management in the market could be overcome.Thus,the production cost of GA could be reduced.The purpose of this study is to study the highest production of GA from different type natural sources such as sugarcane juice and banana in term of fresh and rotten state.The study is ought to investigate the effect of concentration of ethylene glycol (0.2 M to 1 M),temperature (40 ⁰C to 80 ⁰C)and time (30 min to 60 min) on extraction of GA compounds from natural sources and to optimize the production of glycolic acid from the sample after screening using response surface methodology (RSM).The ultrasonic homogenizer was used for the extraction of product with different independent variables.HPLC is used to analyze the concentration of GA in the samples.From the present research,fresh banana peels contain the highest GA concentration at 0.914 M.From RSM the most optimum combination variables are temperature at 70 ⁰C,solvent concentration at 1 M and extraction time at 50 min with desirability 1.000.The optimization of GA can be further investigated by using different types of solvent,extraction method and ultrasonic frequency.